Super courses : the future of teaching and learning - Bain, Ken. (Princeton, N.J. : Princeton University Press, 2021)
"An exploration of some of the most intriguing college teachers' pedagogy, challenging traditional learning environments"--
Part I. The Idea -- Pinning Our Hopes on Our Machines -- How We Learn Part II. The Courses -- A New Kind of University -- Books Behind Bars -- Diverse Classes -- From Charlottesville to Singapore and Beyond : Searching for Super Courses -- Self-Directed Learning and Big Questions : From the DIY Girls to Hurricane Katrina -- Peer Instruction and Then Some -- Remaking a Super Course -- Soup of Interdisciplinary Learning -- Integration of Abilities -- Fostering Growth Mindsets -- A Super Course Department -- A Personal Journey toward a Super Course -- All Knowledge Is Related -- The Pedagogy of Getting Out -- Grades.
Includes bibliographical references and index.
Keywords: College teaching; Education, Higher -- Curricula; Curriculum change; Learning, Psychology of